2011
DOI: 10.1152/ajprenal.00533.2010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of medial calcification on vascular function in uremia

Abstract: The contribution of medial calcification to vascular dysfunction in renal failure is unknown. Vascular function was measured ex vivo in control, noncalcified uremic, and calcified uremic aortas from rats with adenine-induced renal failure. Plasma urea was 16 ± 4, 93 ± 14, and 110 ± 25 mg/dl, and aortic calcium content was 27 ± 4, 29 ± 2, and 4,946 ± 1,616 nmol/mg dry wt, respectively, in the three groups. Maximal contraction by phenylephrine (PE) or KCl was reduced 53 and 63% in uremic aortas, and sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 33 publications
4
25
2
Order By: Relevance
“…To our knowledge, arterial functions have been investigated in one previous study in animals with A-CRF although only the aorta was examined (29). In that study, concentrations of adenine (0.75%) and phosphate in the chow were higher than in the present study, and 0.22% NaCl was added to drinking water.…”
Section: Table 5 Responses To Ach In Mesenteric Arteries Preincubatecontrasting
confidence: 52%
“…To our knowledge, arterial functions have been investigated in one previous study in animals with A-CRF although only the aorta was examined (29). In that study, concentrations of adenine (0.75%) and phosphate in the chow were higher than in the present study, and 0.22% NaCl was added to drinking water.…”
Section: Table 5 Responses To Ach In Mesenteric Arteries Preincubatecontrasting
confidence: 52%
“…This event is the reason for local clot formation and ultimate organ infarction (25). In addition, vascular smooth muscle and endothelial function are altered in renal failure (26). An increased recirculation by a larger AV fistula may result in similar endothelial changes also in other organs at stress such as the heart, indicated by the data in the present study.…”
Section: Discussionsupporting
confidence: 69%
“…The method, it is thought that 2, 8-dihydroxyadenine produced from adenine via oxidization through xanthine dehydrogenase is precipitated in the kidney tubules as kidney stones 13,14) . It has been reported that adenine administration induces chronic tubulointerstitial injury, causing increased plasma creatinine and blood urea nitrogen (BUN) concentrations [15][16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…Animal models of CKD have been previously reported, mostly using rats 12,[15][16][17][18] . The CKD mouse model employed in the current study was induced by feeding the mice a diet containing 0.25% adenine for four weeks, which resulted in increases in the plasma creatinine and BUN concentrations to approximately four and three times that seen in the control mice.…”
Section: Discussionmentioning
confidence: 99%